The inverse of the function f(x) = 2x – 4 is [tex]\mathbf{f^{-1}(x) = \dfrac{x}{2}+2}[/tex]
An inverse of a given function is achieved by replacing the value of x with y, followed by changing the rhythm of the arithmetic operation.
For example; If f(x) posits that we divide three and then add two, the inverse of f(x) will be to remove two then followed by dividing it by three.
From the given information:
[tex]\mathbf{f(x) = 2x - 4}[/tex]
The inverse of the function will be:
Now;
y = 2x - 4
Divide the right-hand side by 2 and changing the arithmetic sign, we have:
[tex]\mathbf{y = \dfrac{x}{2}+ 2}[/tex]
∴
[tex]\mathbf{f^{-1}(x) = \dfrac{x}{2}+2}[/tex]
Therefore, we can conclude that the inverse of the function f(x) = 2x – 4 is [tex]\mathbf{f^{-1}(x) = \dfrac{x}{2}+2}[/tex]
Learn more about the inverse of a function here:
https://brainly.com/question/10300045?referrer=searchResults